FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN PROGRAM POS PEMBINAAN TERPADUPENYAKIT TIDAK MENULAR DI DESA SUNGAI TAWAR KECAMATAN MENDAHARA TANJUNG JABUNG TIMUR TAHUN 2022 - Siti Almar’atus Sholehah; Melda Yenni; Renny Listiawaty (Jurnal Cakrawala Ilmiah, 2023)
Non-communicable diseases have been the leading cause of death in the world since the third millennium. Deaths due to non-communicable diseases amounted to 29 million. In order for non-communicable diseases to continue to increase, the Indonesian government created a program, namely the non-communicable disease guidance post, in order to prevent non-communicable diseases in the community. Sungai Tawar Village is a village with the lowest coverage of integrated coaching posts at 29.7%. The purpose of the study was to determine the factors associated with the utilization of the integrated coaching post program for non-communicable diseases. This study used a cross sectional approach. The research sample was the community in Sungai Tawar Village with a sample size of 80 people. Sampling technique with quota sampling technique. Data were analyzed by chi square test. The results showed that there was a relationship between knowledge, attitudes and the role of cadres with the utilization of the integrated coaching post program for non-communicable diseases in Sungai Tawar Village (p-value <0.03). It is expected that families should always provide encouragement, direction, motivation and guidance to families about the benefits and objectives of the non-communicable disease integrated coaching post for people with non-communicable diseases